ASSOCIATION BETWEEN GINGIVAL ENLARGEMENT AND ANTI HYPERTENSIVE DRUGS- A RETROSPECTIVE STUD - Krishna R, Nivesh; M, Sankari; S, Arvind (International Journal of Psychosocial Rehabilitation, 2020)
Hypertension is also termed as high blood pressure. It can lead to severe health issues thereby increasing the risk of cardiovascular disease, stroke, culminating in death. The force that an individual’s blood is exerted against the ventricular and arterial walls of blood vessels is termed as blood pressure. This pressure is elicited based on the resistance of the blood vessels and how much of the cardiac output is. There are various methods to cope with hypertension such as diet modification, exercise, meditation and medication The aim of the study is to determine the association between gingival enlargement and anti hypertensive drugs.. A very common adverse effect of these drugs is gingival enlargement in the oral cavity. The enlargement of the gums caused due to anti-hypertensive drugs commences, due to their reactions in patients treated with anticonvulsants, immunosuppressants and calcium channel blockers. The data collected from the records were 86000 and they were screened for patients with drug induced gingival enlargement. The collected data was tabulated in excel sheet and imported to spss software for statistical analysis. From the study, 45 patients were diagnosed with drug induced gingival enlargement out of which, 24 patients were males and 21 patients were females. Predominant gender is male. Among the age groups, group 1[20-30 years] had 6 patients, group 2[36-50 years] had 16 patients and group 3[51-70 years] had 23 patients. The predominant age group was group 3[51- 70 years]. Among the type of drug used, gingival enlargement, amlodipine induced gingival enlargement was seen in 78%, nifedipine induced gingival enlargement was seen in 13%. Therefore, to conclude, the predominant drug induced gingival enlargement, was amlodipine in this study and the predominant age group was group 3 [51-70 years].